Small-Scale Wind Power Generator with Inverse Taper and Taper Type Blades at Low Wind Speed - Lubis, Rakhmad Syafutra; Muhayatsyah, Teuku; Syukri, Mahdi; Siregar, Ramdhan Halid; Jalil, Saifuddin Muhammad (Yayasan Kawanad, 2025)
The utilization of wind energy as one of the renewable energy sources in Indonesia is still limited. This is due to Indonesia's large wind potential, but it is at low speeds. One modification of wind turbines to overcome this problem is by using inverse taper and taper blades. Inverse taper blades have a chord distribution that increases from root to tip while taper blades have a chord distribution that decreases from root to tip. This research conducts the design and construction of inverse taper and taper blades on small-scale wind turbines using NACA 6412 airfoil type, then tested in the field and obtained the performance of each blade. The design was carried out using blade element momentum theory to obtain the blade geometry shape and perform performance analysis of each type of blade. Based on the simulation results obtained from QBlade, it shows that the inverse taper blade performance has a maximum Cp of 0.52 while the taper blade has a maximum Cp of 0.41. The power graph from field testing results shows that inverse taper blades provide good power generation at low wind speeds compared to taper blades. The inverse taper blade has a cut-in speed of 1.2 m/s and the best power production occurs at speeds of 1-4 m/s.